2018
DOI: 10.1039/c7cp07406a
|View full text |Cite
|
Sign up to set email alerts
|

Electro-nucleation of water nano-droplets in No Man's Land to fault-free ice Ic

Abstract: Elucidating water-to-ice freezing, especially in "No Man's Land" (150 K < T < 235 K), is fundamentally important (e.g., predicting upper-troposphere cirrus-cloud formation) - and elusive. An oft-neglected aspect of tropospheric ice-crystallite formation lies in inevitably-present electric fields' role. Exploring nucleation in No Man's Land is technically demanding, owing to rapid nucleation rates, to mention nothing of difficulties of applying relevant electric fields thereto. Here, we tackle these intriguing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…, graphene, AgI surface, a face-centered cubic (FCC) Lennard–Jones (LJ) (100) surface, , and (111) surface, a pure hexagonal ice forms on substrates that nucleate nonbasal planes of ice, for example, a LJ (211) FCC surface , and kaolinite. , The formation of stacking ordered ice can be attributed to the ordering of water induced by a substrate that matches the specific stacking sequence of ice polymorph . Interestingly, this notion has also been recently employed in simulations to successfully demonstrate the formation of pure cubic ice, assisted either by special surface geometry or by applying electric field …”
supporting
confidence: 92%
“…, graphene, AgI surface, a face-centered cubic (FCC) Lennard–Jones (LJ) (100) surface, , and (111) surface, a pure hexagonal ice forms on substrates that nucleate nonbasal planes of ice, for example, a LJ (211) FCC surface , and kaolinite. , The formation of stacking ordered ice can be attributed to the ordering of water induced by a substrate that matches the specific stacking sequence of ice polymorph . Interestingly, this notion has also been recently employed in simulations to successfully demonstrate the formation of pure cubic ice, assisted either by special surface geometry or by applying electric field …”
supporting
confidence: 92%
“…When the E increased further, the electric force on the molecules became dominant, elongating the liquid droplets and causing the shape of the droplets to becomes a column, as shown in Figure 3h. Antonio et al [42] have also observed the stretch of liquid water under an electric field in their experiments. This can also be confirmed by the molecular dipole distribution shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…They have found that both the electric field direction and strength could affect the viscosity of water. The wetting properties of water droplets on a surface can also be manipulated by the electric field due to the characteristics of water, including droplet spreading [39], droplet morphology transformation [40,41,42], and contact angle variation [43,44]. The potential application of an electric field on phase changes has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the measured hydroxyl distances in AFGP-8 range between~3.455 Å to~5.518 Å. Previous studies have shown that molecular dynamics simulations are an effective tool for understanding how antifreeze compounds bind to and interact with ice as it nucleates [19][20][21][22][23][24]. Building upon this data, this study uses molecular dynamics simulations to investigate how the hydroxyl distances on the sugar moieties of AFGP may affect its ice nucleation inhibition and ice-binding properties.…”
Section: Introductionmentioning
confidence: 95%